The Relationship Between The Role of Husband's Accompaniment To The Success of Exclusive Breastfeeding in Children Aged 6-23 Months - Tiara Wuri Handayani; Puri Kresna Wati; Marni Br Karo (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
Slow growth and death experienced by infants are caused by breastfeeding problems. Exclusive breastfeeding is an important factor in preventing infectious diseases, malnutrition, and infant mortality. Breast milk is a liquid that is removed directly from the mother's breast for the baby. Breast milk contains the nutrients and fluids that babies need in their first 6 months. The husband plays a role in the success of exclusive breastfeeding, namely as a breastfeeding father. The role of the husband in the process of exclusive breastfeeding makes it easy for the mother because the husband can create peace and comfort when the mother breastfeeds her baby. This study aims to determine whether there is a relationship between the role of the husband's assistance and the success of exclusive breastfeeding in children aged 6-23 months at the Sriamur Health Center in 2023. The research method used is analytic observational with a cross-sectional approach. The population of this study were fathers who had children aged 6-23 months at the Sriamur Health Center. This research has gone through an ethical review process. A sampling of this study used an accidental sampling technique with a total sample of 191 respondents. The data analysis used is SPSS with the Chi-Square test. The results of this study found that 131 respondents (68.58%) gave exclusive breastfeeding and received a positive husband's mentoring role. Conclusion: The results of the statistical test showed a p-value = 0.001 0.05, which means there is a relationship between the husband's accompanying role on the success of exclusive breastfeeding.